2019
DOI: 10.1111/wvn.12413
|View full text |Cite
|
Sign up to set email alerts
|

External Facilitation as an Evidence‐Based Practice Implementation Strategy During an Antibiotic Stewardship Collaborative in Neonatal Intensive Care Units

Abstract: Background: Despite research support, evidence-based practices (EBPs) are inconsistently implemented throughout the United States. Facilitation is one implementation strategy to speed adoption in clinical settings. Facilitation has not been previously described in the literature as an implementation strategy within neonatal care.Purpose: The purpose of this study was to categorize and describe essential features of facilitation in the context of implementing an EBP using perspectives elicited from neonatal cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…In the i-PARHIS framework, it is essential to consider all implementation components beyond just the evidence (i.e., unit context and resources needed to implement; Harvey & Kitson, 2016). Our findings are consistent with facilitation studies in adult and neonatal care contexts that showed context and resources were also important to success (Harvey, McCormack, Kitson, Lynch, & Titchen, 2018;Quinn, Gephart, & Davis, 2019). NICU resources varied regarding time for QI, availability of NICU-specific lactation support and nursing education, donor human milk, and donor-based human milk fortifiers.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In the i-PARHIS framework, it is essential to consider all implementation components beyond just the evidence (i.e., unit context and resources needed to implement; Harvey & Kitson, 2016). Our findings are consistent with facilitation studies in adult and neonatal care contexts that showed context and resources were also important to success (Harvey, McCormack, Kitson, Lynch, & Titchen, 2018;Quinn, Gephart, & Davis, 2019). NICU resources varied regarding time for QI, availability of NICU-specific lactation support and nursing education, donor human milk, and donor-based human milk fortifiers.…”
Section: Discussionsupporting
confidence: 82%
“…Casebased learning allowed real, de-identified NEC cases to be discussed, which ultimately spurred discussion and sharing of strategies to prevent NEC. All units were retained through the series, which was rare when compared to other neonatal collaboratives that used a facilitation model (Quinn et al, 2019). One potential reason for our retention of units could be due to the external facilitation provided by the hub and inclusion of IFs as core team members.…”
Section: Study Strengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other barriers include a lacking organizational culture which encourages and promotes the use of EBP. Quinn et al [28] reported that facilitator stewardship, evaluation strategies, supportive culture, organization receptivity, and facilitated change management are needed for the appropriate implementation of EBP. A lack of awareness of EBP is one of the foremost barriers to applying it.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrate that practice facilitation increases the likelihood of success of QI initiatives, increases provider adherence to evidence-based guidelines, and improves care quality metrics in a broad array of clinical settings [8][9][10][11]. Practice facilitation has been used to effectively support implementation of evidence-based behavioral health interventions [12,13], integrated behavioral health and primary care [14], colorectal screening [15], antibiotic stewardship [16], pediatric preventive care [11], and implementation of patient-centered medical home programs [17][18][19].…”
Section: Introductionmentioning
confidence: 99%